METAPHOR AS ASEMANTIC RESOLUTION OF MUSICAL EDUCATION: PHENOMENOLOGICAL INSIGHTS - Venslovaitė, Vita (Acta Paedagogica Vilnensia, 2013)
This article emphasizes the meaning and value of a metaphor in the educational process. Referring to the education specialist D. E. Denton, the article demonstrates that considering a metaphor as a new and unique meaning in the designation of experience and also as the fact that the entire existential language concerning the ordinary experience is metaphorical, it is very important to develop metaphorical thinking. The article describes also the musical phenomenon which comprises a new meaning or knowledge because it affects every person individually depending on his / her experience. The description of the musical phenomenon is inseparable from the human experience in music. The metaphorically designated musical experience always constitutes a new meaning in the vast horizon of experience. The metaphor, as shown by the results of an empirical phenomenological research, is essential in the designation of experience and in the transfer of the musical meaning during the musical education process. Metaphors are used to designate sounds, rhythm, musical phrases, to characterise the melody and the character of a piece of music, to create new formations – and all this for a student to be able to perceive and later to designate new meanings through his or her own experience. The musical meaning, different each time and related to a unique individual experience, offers an opportunity to explore oneself and one’s inner world and to perceive the limitless potential of the musical givenness.